Fatigue and Dyspnoea as Main Persistent Post-COVID-19 Symptoms in Previously Hospitalized Patients: Related Functional Limitations and Disability - Fernández de las Peñas, César; Palacios Ceña, Domingo; Gómez Mayordomo, Víctor; Palacios Ceña, María; Rodríguez Jiménez, Jorge; de la Llave Rincón, Ana I.; Velasco Arribas, María; Fuensalida Novo, Stella; Ambite Quesada, Silvia; Guijarro, Carlos; Cuadrado, María L.; Florencio, Lidiane L.; et al. (My University, 2021)
Background: Multicentre studies focussing on specific longterm post-COVID-19 symptoms are scarce. Objective: The aim of this study was to determine the levels of fatigue and dyspnoea, repercussions on daily life activities, and risk factors associated with fatigue or dyspnoea in COVID-19 survivors at long term after hospital discharge. Methods: Age, gender, height, weight, symptoms at hospitalization, preexisting medical comorbidity, intensive care unit admission, and the presence of cardio-respiratory symptoms developed after severe acute respiratory syndrome coronavirus 2 infection were collected from patients who recovered from COVID-19 at 4 hospitals in Madrid (Spain) from March 1 to May 31, 2020 (first COVID-19 wave). The Functional Impairment Checklist was used for evaluating fatigue/dyspnoea levels and functional limitations. Results: A total of 1,142 patients (48% women, age: 61, standard deviation [SD]: 17 years) were assessed 7.0 months (SD 0.6) after hospitalization. Fatigue was present in 61% patients, dyspnoea with activity in 55%, and dyspnoea at rest in 23.5%. Only 355 (31.1%) patients did not exhibit fatigue and/or dyspnoea 7 months after hospitalization. Forty-five per cent reported functional limitations with daily living activities. Risk factors associated with fatigue and dyspnoea included female gender, number of pre-existing comorbidities, and number of symptoms at hospitalization. The number of days at hospital was a risk factor just for dyspnoea. Conclusions: Fatigue and/or dyspnoea were present in 70% of hospitalized COVID-19 survivors 7 months after discharge. In addition, 45% patients exhibited limitations on daily living activities. Being female, higher number of pre-existing medical comorbidities and number of symptoms at hospitalization were risk factors associated to fatigue/dyspnoea in COVID-19 survivors 7 months after hospitalization.
Keywords: COVID-19 · Fatigue · Dyspnoea · Function · Risk factors